Modeling re-absorption of fluorescence from the leaf to the canopy level - Romero, Juan Manuel (2017)
Chlorophyll fluorescence is widely used as an indicator of photosynthesis and physiological state of plants. Remote acquisition of fluorescence allows the diagnosis of large field extensions, even from satellite measurements. Nevertheless, fluorescence emerging from chloroplasts, the one directly connected to plant physiology, undergoes re-absorption processes both within the leaf and the canopy. Therefore, corrections of the observed canopy fluorescence, taking into account these two re-absorption processes may help to draw accurate inferences about plant health. Here, we show the theoretical development and experimental validation of a model that allows to retrieve the spectral distribution of the leaf fluorescence spectrum from that on top of canopy (TOC) using a correction factor which is a function of both canopy and soil reflectance, and canopy transmittance. Canopy fluorescence spectra corrected by our theoretical approach and normalized shows 95% correlation with the normalized fluorescence spectrum at leaf-level, thus validating the model. Therefore, our results provide a physical explanation and quantification for fluorescence re-absorption within the canopy, a phenomenon which has only been mentioned but never measured up to the date. From a more general perspective, this new analytical tool together with the one previously developed by Ramos and Lagorio (2004) allows to obtain the spectral distribution of chloroplast fluorescence spectrum from that on top of canopy (TOC).